Requirements and Control Simulation of Flap Electronic Control Unit for Civil Aircraft - HAN Sai; SUN Junshuai; HUA Dongsheng (Hangkong gongcheng jinzhan, 2020)
The flap system is one of the significant systems in an aircraft, and the flap electronic control unit is the core component, so the study on requirement of aircraft performance and safety is of great importance. Aiming at the flap electronic control unit, the design inputs in terms of function requirements, performance requirements and interface requirements are introduced. The flap system architecture and working principle for civil aircraft are surmised, and the control logic for system's normal working and fault protection is analyzed. The Stateflow of Simulink is used to simulate the conversion of working modes, and the user interface is built by GUI. The simulation results indicate that the design parameters of constraint conditions between the working modes of the flap electronic control unit, control law of the flaps retraction and extension, and motor's accelerated speed parameters at each stage can meet the requirements, and can provide the reference for the civil aircraft flap control system design.